The Effectiveness of Cognitive-Behavioral Therapy on Academic Procrastination and Academic Anxiety in Adolescents of Divorced Families - Chehrazi, Keihaneh; Namdari , Maryam; Hashempoor Malakshah, Somayeh; Poorsheykhian , Sudabeh; Hakak, Bahare (Mental Health and Lifestyle Journal, 2024)
The present study aimed to investigate the effectiveness of cognitive-behavioral therapy (CBT) in reducing academic procrastination and academic anxiety among adolescents from divorced families. This research employed a quasi-experimental design with a pretest-posttest control group. The statistical population included adolescents from divorced families who visited a counseling and psychological services clinic in Tehran in 2023. Using a convenience sampling method, 30 participants were selected and randomly assigned to experimental and control groups. The experimental group received eight 90-minute sessions of cognitive-behavioral training, while the control group continued with routine activities. Data were collected using the Academic Procrastination Scale (Solomon & Rothblum, 1984) and the Sarason Test Anxiety Questionnaire (1957). Data analysis was performed using descriptive statistics, the Kolmogorov–Smirnov test for normality, and univariate ANCOVA to compare posttest scores across groups while controlling for pretest scores. The results revealed significant differences between the experimental and control groups in posttest scores. After controlling for pretest scores, the ANCOVA showed that cognitive-behavioral therapy significantly reduced academic procrastination (F(1,27) = 16.63, p = .005, η² = .41) and academic anxiety (F(1,27) = 14.32, p = .005, η² = .34) in the experimental group. These findings suggest a meaningful impact of the intervention on the targeted psychological outcomes. Cognitive-behavioral therapy is an effective intervention for reducing academic procrastination and academic anxiety in adolescents from divorced families. By improving self-regulation and coping skills, CBT helps adolescents manage emotional distress and enhances academic functioning. These findings support the implementation of CBT in school and clinical settings for at-risk youth populations.